Fuzzy Optimization and Decision Making A Journal of Modeling and Computation Under Uncertainty - Fang, Shu-Cherng.; Liu, Baoding; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
The key objective of Fuzzy Optimization and Decision Making is to promote research and the development of fuzzy technology and soft-computing methodologies to enhance our ability to address complicated optimization and decision making problems involving non-probabilitic uncertainty. The journal will cover all aspects of employing fuzzy technologies to see optimal solutions and assist in making the best possible decisions. It will provide a global forum for advancing the state-of-the-art theory and practice of fuzzy optimization and decision making in the presence of uncertainty. Any theoretical, empirical, and experimental work related to fuzzy modeling and associated mathematics, solution methods, and systems is welcome. The goal is to help foster the understanding, development, and practice of fuzzy technologies for solving economic, engineering, management, and societal problems. The journal will provide a forum for authors and readers in the fields of business, economics, engineering, mathematics, management science, operations research, and systems. The journal will consider papers for publication in the following areas: Modeling: Papers formulating problems involving uncertainty as a mathematical model in the context of fuzzy optimization and decision making. Often these papers will address the suitability, validity and advantages of using fuzzy technologies to treat real-life problems. Theoretical Developments: Papers establishing mathematical theory on fundamental issues. Often these papers will address the existence and properties of fuzzy optimal solutions or fuzzy optimal decisions. Algorithmic Developments: Papers presenting solution methods and/or studying their computational complexity. Often these papers will propose new algorithms to solve fuzzy optimization and decision making problems in an effective and efficient manner. Systems Development and Applications: Papers describing the development of a software/ hardware system and documenting the benefits achieved in practical application. The papers often deal with innovative system implementations and applications for which no previous solutions exist or for which improvement is achieved over previous solutions. Manuscript submitted to the journal may cover one or several areas. The journal will also publish invited "state-of-the-art" surveys on specific topics. The research and practice of fuzzy optimization and decision making for special interests groups and special geographic locations will be accommodated by publishing special issues with guest editors. Officially cited as: Fuzzy Optim Decis Making.
Keywords: Operations research; Decision making; Mathematical logic; Mathematical optimization; Calculus of variations; Probabilities; Mathematical Logic and Foundations; Probability Theory and Stochastic Processes; Optimization; Calculus of Variations and Optimal Control; Optimization; Artificial Intelligence; Operations Research/Decision Theory